2012
DOI: 10.1111/j.1365-2109.2012.03148.x
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density effects on growth and production of the threatened silurid catfish,Mystus cavasius(Hamilton) fingerlings in nursery ponds

Abstract: The fingerling‐rearing experiment of the threatened catfish, Mystus cavasius was carried out at different stocking densities in earthen nursery ponds. Twelve‐day‐old fry were stocked at 200 000 ha−1 in treatment‐1 (T1), 250 000 ha−1 in treatment‐2 (T2) and 300 000 ha−1 in treatment‐3 (T3) respectively. The mean length and weight of fry at stocking was 1.24 ± 0.25 cm and 0.11 ± 0.04 g respectively. Fry in all the experimental ponds were supplemented with SABINCO nursery feed for the first 14 days and starter‐I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
5
18
2
Order By: Relevance
“…M. cavasius is omnivorous with a dietary preference for macro invertebrates (Chaturvedi and Parihar, 2012). A specific growth rate of around 2.7% per day is reported for the species at stocking densities of 2 lakhs per ha (Rahman et al, 2013) which is comparable to that reported for Heteroclarias (Okunsebor and Ayuma, 2011) and Clarias gariepinus (Marimuthu et al, 2010). Since they attain table size in a short…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…M. cavasius is omnivorous with a dietary preference for macro invertebrates (Chaturvedi and Parihar, 2012). A specific growth rate of around 2.7% per day is reported for the species at stocking densities of 2 lakhs per ha (Rahman et al, 2013) which is comparable to that reported for Heteroclarias (Okunsebor and Ayuma, 2011) and Clarias gariepinus (Marimuthu et al, 2010). Since they attain table size in a short…”
Section: Introductionsupporting
confidence: 70%
“…Reduction of water column to 8 to 10 cm to prevent fatal exhaustion of the fry was done immediately after spawning as recommended for air breathing catfish nursery rearing (Potongkam and Miller, 2006).Successful nursery rearing in earthen ponds was reported for 12 day old M. cavasius for two months (Rahman et al, 2013). However we observed that fry were better equipped survive in deeper waters at 18 days age when they became facultative air breathers.…”
Section: Larval Rearingmentioning
confidence: 68%
“…; Sharma & Chakrabarti ; Rahman, Mazid, Rahman, Khan, Hossain & Hossain ; Sahu et al . ; Rahman, Zaher & Azimuddin ; Das, Jena, Mishra & Pati ; Rahman, Zaher, Azimuddin, Yeasmine, Khan & Arshad ). However, it was interesting to note that despite presence of greater number, the SGR, length and weight attainment of seed in T‐2 were similar to those in T‐1 ( P > 0.05) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since information on the bionomics (Qayyum, and Qasim 1965;Goswami and Dasgupta 2007), growth and feeding behaviour (Sivakami 1982;Taleb et al 1991;Hanjavanit and Sangpradub 2009), reproductive physiology (Parameswaran et al 1970), breeding biology (Chakrabarti et al 2007;Rahman et al 2008;Vijayakumar 2010), spawning behaviour (Parameswaran et al 1971;Chakrabarti et al 2006), chromosomal structures (Rishi et al 1994;Sharma 2008), induced spawning ( Sridhar et al 2008;Banik 2010a, 2011a, b, Banik et al 2011, 2012 and on embryonic and larval development (Chakrabarti et al 2007) are available. In the present study an attempt has been made to develop the technique to enhance the survival as well as growth rate of O. pabda under designed culture conditions.…”
Section: Introductionmentioning
confidence: 98%